Bioactivity of Gutta flow II versus Modified Gutta Percha based Silicon Endodontic Sealers by Nanobioactive Fillers - Saad A. Ramadhan1 , Raghad A. Al hashimi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The success of endodontic therapy is relied on radicular system cleaning, shaping, elimination of micro-organisms, and three dimensional filling of the radicular complex.This study was conducted to develop and assess new root canal sealer incorporating nano-sized bioactive glass into Gutta Flow II. The following concentration was used depend on a pilot study included adding (3%) of 45S5 bioactive glass into the Gutta Flow II. These materials were tested through assessment bioactivity. bioactivity test was undertaken after immersion of the tested samples into PBS for three days, seven days, fourteen days, and twenty eight days using FTIR too. study was found that it’s peaks was appear at level 800-1000 cm-1. The results showed that GFII group revealed no peak at the 910 cm-1, while, while BG3% revealed 179.85 pixel height, in conclusion the newly developed sealers exhibited apparent apatite and apatite precursor forming ability significantly with BG 3% while GuttaFlow II sealer showed no apatite layer forming ability.